« Je ne bégaierai pas… et je serai une fille » : les apories de l’autoreprésentation culturelle en tant que femme trans qui bégaie dans Crossing - Raphaël Jacques (Glad!)
The last decade has witnessed the emergence of dysfluency studies, a burgeoning field dedicated to shedding light on the experience of stuttering through an anti-ableist lens. The reflections that have taken place have, however, shown little interest in gender, in general, and transness, in particular. The memoirs of American trans stuttering thinker Deirdre McCloskey challenge this gap. Within their pages, the writer conceives transfeminity and stuttering in a resolutely aporetic relationship. This exploratory article sets out to unravel this oppositional relationship, by first addressing the conception of stuttering as an (inter)subjective barrier to the performance of successful femininity. Secondly, the joint psychiatrization of transness and stuttering is examined in order to expose the mobilization of psychopathologizing discourses for the purpose of reinforcing the gatekeeping of gender-affirming care for trans stutterers.